Neurological Mechanisms of Animal-Assisted Intervention in Alzheimer’s Disease: A Hypothetical Review - Kim, Sujin; Nam, Yunkwon; Ham, Min-Joo; Park, Chisoo; Moon, Minho; Yoo, Doo-Han (Frontiers in Aging Neuroscience, 2021)
Alzheimer’s disease (AD) is an irreversible neurodegenerative brain disorder with aggregation of amyloid-beta (Aβ) and tau as the pathological hallmarks. AD is the most common form of dementia and is characterized by a progressive decline of cognition. The failure of pharmacological approaches to treat AD has resulted in an increased focus on non-pharmacological interventions that can mitigate cognitive decline and delay disease progression in patients with AD. Animal-assisted intervention (AAI), a non-pharmacological intervention, improves emotional, social, and cognitive dysfunction in patients with neurodegenerative diseases. In particular, AAI is reported to mitigate the effects of cognitive impairment in patients with AD. Despite the positive effects of AAI on cognitive dysfunction in patients with AD, there have been no studies on how AAI affects AD-related pathologies. This review postulates potential neurological mechanisms of emotional or social interaction through AAI in countering AD-related pathologies, such as Aβ deposition, tau hyperphosphorylation, neuroinflammation, and impaired adult hippocampal neurogenesis (AHN), and proposes insights for future research by organizing accumulated previous evidence.